Thinking beyond Vaccination: Promising Add-On Strategies to Active Immunization and Vaccination in Pandemics—A Mini-Review - Tatzber, Franz; Wonisch, Willibald; Resch, Ulrike; Strohmaier, Wolfgang; Lindschinger, Meinrad; Mörkl, Sabrina; Cvirn, Gerhard (Viruses, 2023)
There is little doubt that final victories over pandemics, such as COVID-19, are attributed to herd immunity, either through post-disease convalescence or active immunization of a high percentage of the world’s population with vaccines, which demonstrate protection from infection and transmission and are available in large quantities at reasonable prices. However, it is assumable that humans with immune defects or immune suppression, e.g., as a consequence of allograft transplantation, cannot be immunized actively nor produce sufficient immune responses to prevent SARS-CoV-2 infections. These subjects desperately need other strategies, such as sophisticated protection measures and passive immunization. Hypertonic salt solutions attack vulnerable core areas of viruses; i.e., salt denatures surface proteins and thus prohibits virus penetration of somatic cells. It has to be ensured that somatic proteins are not affected by denaturation regarding this unspecific virus protection. Impregnating filtering facepieces with hypertonic salt solutions is a straightforward way to inactivate viruses and other potential pathogens. As a result of the contact of salt crystals on the filtering facepiece, these pathogens become denatured and inactivated almost quantitatively. Such a strategy could be easily applied to fight against the COVID-19 pandemic and other ones that may occur in the future. Another possible tool to fight the COVID-19 pandemic is passive immunization with antibodies against SARS-CoV-2, preferably from human origin. Such antibodies can be harvested from human patients’ sera who have successfully survived their SARS-CoV-2 infection. The disadvantage of a rapid decrease in the immunoglobulin titer after the infection ends can be overcome by immortalizing antibody-producing B cells via fusion with, e.g., mouse myeloma cells. The resulting monoclonal antibodies are then of human origin and available in, at least theoretically, unlimited amounts. Finally, dry blood spots are a valuable tool for surveilling a population’s immunity. The add-on strategies were selected as examples for immediate, medium and long-term assistance and therefore did not raise any claim to completeness.